Article Review: The 18th Century Aesthetics and Their Associations with Landscape Architecture and Environmental Art - Selanon, Pattamon; Srilertchaipanij, Hansa; Saleh-Bala, Maimuna (Journal of Architectural/Planning Research and Studies (JARS), 2019)
The beautiful, the sublime, and the picturesque were three key concepts of aesthetics originated in philosophical context of the 18th century. Together, they outlined the variety of aesthetically significant experiences. The article aims to review historical roots of the three aesthetics and how they were associated with landscape architecture and environmental art, both of which concerned with shaping the land and environment. Subsequently, the article discusses associations between the English Landscape School - landscape architecture embraced by the 18th century three aesthetics and the ecological design - modern landscape architectural design theme primarily dominated by Ian McHarg in the 1960s. Conclusively, the article critically discussed lessons learned from the associations and how landscape architecture should be shaped forward.